"I've Got Better Things to Worry About": Police Perceptions of Graffiti and Street Art in a Large Mid-Atlantic City. (June 2014) - Ross, Jeffrey Ian; Wright, Benjamin S.
The majority of scholarly research on graffiti and street art has examined this phenomenon in terms of its distribution and the nature of the perpetrators. Rarely has the law enforcement response been investigated. To better understand this neglected aspect, the investigators constructed a survey that they administered to a sample of officers in a large Mid-Atlantic police department to determine their attitudes, in particular their perceptions, regarding graffiti, street art, and perpetrators of this behavior. The survey takes into consideration important police-related variables and situational factors to provide a portrait of officer perceptions. The major finding indicates that the shift and race of police officers might have an influence on their decisions to stop, question, and arrest suspects on graffiti and street art vandalism-related charges. This is consistent with other studies of police perceptions of illegal behavior.